(untitled) (Advancements in Homeopathic Research, 2022)
This treatise is endeavored to elucidate the efficacy of Hahnemann’s susceptibility based latest and renewed dosage techniques with which he achieved his long time aspiration, ‘Ideal Cure’. Hahnemann’s shift from single dose to split dose has been justified with the purpose of introducing Homoeopathy as fastest & safest therapeutic system in the world. Current demand in ideal repetition of Homoeopathic similar medicine in many cases becomes readily apparent to mind while reading this comprehensible write up.